The newest and the oldest species in the same vial: Description of a new species of Ceratomontia Roewer, 1915 and redescription of Ceratomontia capensis Roewer, 1915 (Opiliones: Laniatores: Triaenonychidae) - Porto, Willians; Pérez-González, Abel (Zootaxa, 2023)
Ceratomontia starengai sp. nov. is described from South Africa, based on one specimen found in the type series of Ceratomontia capensis Roewer, 1915, which is redescribed in this work. The presence of this new species represents sympatry of Ceratomontia species, something not uncommon for species of the family Triaenonychidae. Images of the genital morphology, which are crucial to the diagnosis of the group, are included in the descriptions.